Seminar Digital Marketing untuk Mendorong Inovasi Strategi Pemasaran pada UMKM - Hasanah, Huswatun; Nofiyanti, Bela; Salsa, Cinta Tasya; Wahyuni, Indah Tri; Fitriani, Leni (Universitas Methodist Indonesia, 2024)
In the current digital era, digital marketing has become a vital tool for the development of business The digital marketing seminar was held as an effort to increase the knowledge and skills of Micro, Small and Medium Enterprises (MSMEs) players in optimizing digital technology to expand market reach and increase sales. This research aims to evaluate the effectiveness of digital marketing seminars in improving the digital capabilities of MSME players and analyze the long-term impact of the knowledge gained.